Williams Ginecología - Hoffman, Barbara L.; Schorge, John O.; Halvorson, Lisa M.; Hamid, Cherine A.; Corton, Marlene M.; Schaffer, Joseph I. (McGraw-Hill's AccessMedicina., 2020)
Williams. Gynecology provides a comprehensive, evidence-based presentation of the depth and breadth of gynecology. Section 1 covers general gynecology topics. Section 2 contains chapters covering the endocrinology of reproduction and sterility. Section 3 presents the developing field of medicine and reconstructive surgery of the female pelvis. While in section 4 gynecological oncology is addressed.